Scoping Review: Hubungan Prematur dengan Kejadian Stunting pada Anak Usia di Bawah 5 Tahun - Diva Satrinabilla Armawan; Habib Syarif Hidayatuloh; Cice Tresnasari; Susanti Dharmmika (UNISBA Press, 2022)
Abstract. Stunting is a growth disorder in children caused by chronic or repeated malnutrition, recurring infections, inadequate psychosocial stimulation. In 2019, WHO said the prevalence of stunting was 21.3% worldwide. One of the most common causes of stunting is chronic malnutrition, which can be caused by conditions in the fetus, premature birth or stunted growth. Children under five who are born prematurely have an increased risk of stunting in the first two years of life. The purpose of this study was to determine the relationship between premature birth and stunting in children under 5 years of age. This study used the Scoping Review method, searching for articles from databases such as PubMed, SpringerLink, ScienceDirect, ProQuest, Ovid and Google Scholar using the keywords (